2016
DOI: 10.1111/cpf.12330
|View full text |Cite
|
Sign up to set email alerts
|

Upper limbs total occlusion pressure assessment: Doppler ultrasound reproducibility and determination of predictive variables

Abstract: Total occlusion pressure (TOP) is an important variable to ischaemic exercise training because the optimal pressure of flow restriction (OPR), applied during this exercise modality, is derived from it. Despite the common use of Doppler ultrasound (DU) to determine the TOP, the reproducibility of this assessment was not evaluated yet. Given this, the objective was to evaluate the reproducibility of DU for the measurement of TOP in upper limbs and determine the predictive variables. Thirteen male volunteers atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 25 publications
2
35
0
Order By: Relevance
“…3,17,27,37,46,48,79 Currently, it is recommended that individual occlusion pressures be calculated as a percentage of the total arterial occlusion pressure (AOP), with individual protocols ranging from 60% to 80%. 35,40,69,84 The gold standard method of measuring AOP and true occlusion is Doppler ultrasound, 6,9,29,56,66 although recent investigations have begun to assess the feasibility of pulse oximetry as a lower maintenance alternative. 77,84 A previous method in the literature attempted to predict the AOP as a percentage of the brachial systolic blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…3,17,27,37,46,48,79 Currently, it is recommended that individual occlusion pressures be calculated as a percentage of the total arterial occlusion pressure (AOP), with individual protocols ranging from 60% to 80%. 35,40,69,84 The gold standard method of measuring AOP and true occlusion is Doppler ultrasound, 6,9,29,56,66 although recent investigations have begun to assess the feasibility of pulse oximetry as a lower maintenance alternative. 77,84 A previous method in the literature attempted to predict the AOP as a percentage of the brachial systolic blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…The TOP of dominant arm was determined as the lowest pressure necessary to occlude completely the blood flow, and the partial occlusion pressure was set as the value corresponding to 50% of TOP. The complete proceedings (i.e., the sequence of insufflations until to achieve the TOP) was described by Morais et al [21] which found a good reproducibility for the TOP determination. The TOP determination was carried out only one time for each subject.…”
Section: Total Occlusion Pressure Determinationmentioning
confidence: 99%
“…Calculation of arterial occlusive pressure (AOP) involves determination of the pressure required to fully occlude arterial flow to the involved limb ( AORN Recommended Practices Committee, 2007 ). This is most often achieved using Doppler ultrasound ( Bezerra de Morais et al, 2016 ) and can be used to prescribe pressure at a relative percentage of AOP to standardise the level of occlusion across cohorts ( Laurentino et al, 2012 ; Hughes et al, 2017 ; Patterson et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%